Tinjauan Hukum Islam terhadap Penerapan Pembayaran Royalti Buku - Nurul Izzah; Nandang Ihwanudin; Yayat Rahmat Hidayat (Bandung Conference Series: Sharia Economic Law, 2023)
Abstract. Royalties are compensation for the use of the economic rights of a work or related product received by the creator or owner of the related right. There are differences of opinion regarding the payment of royalties based on a syirkah contract. This study aims to determine the application of book royalty payments in terms of Islamic law. The method used is qualitative and the type of research is field research and literature. The data collection technique used was interviews with managers of Magama Publishing publishers and Despersa writers. The data sources used come from primary and secondary data sources and are then analyzed using a normative juridical analysis approach. The object of this research is the payment of book royalties at publishers. The results of this study are that the amount of royalties given to writers ranges from 7% - 15%. Royalties will be paid after the book is published until the contract period expires. The practice of paying book royalties at Magama Publishing is in accordance with the views of the scholars, whether the distribution of royalties is based on an agreement or the distribution of royalties based on capital. Abstrak. Royalti adalah imbalan atas pemanfaatan hak ekonomi suatu ciptaan atau produk terkait yang diterima oleh penipta atau pemilik hak terkait. Terdapat perbedaan pendapat tentang pembayaran royalti berdasarkan akad syirkah. Penelitian ini bertujuan untuk mengetahui penerapan pembayaran royalti buku yang ditinjau dari hukum Islam. Metode yang diterapkan yakni kualitatif dan jenis penelitiannya penelitian lapangan dan kepustakaan. Teknik pengumpulan data yang digunakan yaitu wawancara terhadap pengelola penerbit Magama Publishing dan penulis Despersa. Sumber data yang digunakan berasal dari sumber data primer dan sekunder kemudian dianalisis menggunakan pendekatan analisis yuridis normatif. Adapun yang menjadi objek dalam penelitian ini adalah tentang pembayaran royalti buku di penerbit. Hasil penelitian ini yaitu besaran royalti yang diberikan untuk penulis berkisar 7% - 15%. Royalti akan dibayarkan setelah buku diterbitkan hingga masa kontrak habis. Praktik pembayaran royalti buku di Magama Publishing sudah sesuai dengan pandangan para ulama baik pembagian royalti berdasarkan kesepakatan ataupun pembagian royalti berdasarkan modal.